Returning to work after sickness absence due to common mental disorders: study design and baseline findings from an 18 months mixed methods follow-up study in Germany - Alexandra Sikora; Gundolf Schneider; Ralf Stegmann; Uta Wegewitz (BMC, 2019)
Abstract Background With nearly 30 % of the general population experiencing one mental disorder in 12 months, common mental disorders (CMDs) are highly prevalent in Germany and mainly affect the workforce. Therefore, the processes of successfully returning to work (RTW) and achieving a sustainable RTW (SRTW) are important not only for recovery but the prevention of negative consequences like job loss or disability retirement. While factors influencing and predicting the time until RTW are well-investigated in other countries, research on determinants of RTW and SRTW has received little attention in Germany. Consequently, this study aims to investigate the RTW and SRTW processes due to CMDs from the employees´ perspective in Germany. Methods This prospective cohort study uses a convergent parallel mixed methods design with a quantitative sample and qualitative sub-sample. Two hundred eighty-six participants of the quantitative study and a sub-sample of 32 participants of the qualitative study were included. The primary outcome of the quantitative study is the time until RTW and full RTW. The secondary outcome is the sustainability of RTW. The following measures will be used to cover work-, RTW- and health-related factors: working time, duration of sickness absences, functional ability, work ability, RTW self-efficacy, social support, work-privacy conflict, job satisfaction, job crafting and depressive symptoms. Quantitative and qualitative data will be integrated at the end. Discussion The paper provides an overview on study design, recruitment, sample characteristics and baseline findings of an 18 months mixed methods follow-up study in Germany. This study will provide evidence of (S)RTW processes and its influencing factors due to CMDs in Germany and therefore contribute to further improvement of its (S)RTW practices. Trial registration German Clinical Trials Register (ID: DRKS00010903, July 28, 2017, retrospectively registered).